The association between biological rhythms, depression, and functioning in bipolar disorder: a large multi‐center study. (22nd May 2015) - Pinho, M.; Sehmbi, M.; Cudney, L. E.; Kauer‐Sant'anna, M.; Magalhães, P. V.; Reinares, M.; Bonnín, C. M.; Sassi, R. B.; Kapczinski, F.; Colom, F.; Vieta, E.; Frey, B. N.; et al.
Abstract : Objective: We examined the relationship between biological rhythms and severity of depressive symptoms in subjects with bipolar disorder and the effects of biological rhythms alterations on functional impairment. Method: Bipolar patients ( n = 260) and healthy controls ( n = 191) were recruited from mood disorders programs in three sites (Spain, Brazil, and Canada). Parameters of biological rhythms were measured using the Biological Rhythms Assessment in Neuropsychiatry (BRIAN), an interviewer administered questionnaire that assesses disruptions in sleep, eating patterns, social rhythms, and general activity. Results: Multivariate analyses of covariance showed significant intergroup differences after controlling for potential confounders (Pillai's F = 49.367; df = 2, P < 0.001). Depressed patients had the greatest biological rhythms disturbance, followed by patients with subsyndromal symptoms, euthymic patients, and healthy controls. Biological rhythms and HAMD scores were independent predictors of poor functioning ( F = 12.841, df = 6, P < 0.001, R 2 = 0.443). Conclusion: Our study shows a dose‐dependent association between the severity of depressive symptoms and degree of biological rhythms disturbance. Biological rhythms disturbance was also an independent predictor of functional impairment. Although the directionality of this relationship remains unknown, our results suggest that stability of biological rhythms should be an important target of acute and long‐term management of bipolar disorder and may aid in the improvement of functioning.